Tuning and performance comparison of multiresonant piezoelectric shunts. (November 2022) - Raze, Ghislain; Dietrich, Jennifer; Kerschen, Gaetan
This work presents tuning rules for piezoelectric shunts aiming to mitigate multiple structural resonances. Starting from a specification procedure of the shunt characteristics, the electrical parameters are derived for shunt topologies proposed in the literature, namely Hollkamp's shunt, the current flowing shunt, the series parallel impedance structure and the current blocking shunt. Effective vibration mitigation of multiple structural modes is demonstrated numerically and experimentally on a piezoelectric beam. Performance in terms of vibration reduction obtained with the different shunts is shown to be comparable if similar shunt characteristics are considered.